Gandhi handbook - Jain, Manik 1938-; Ray, Mrinal Kanti (Kolkata Philatelia, 2006)
Handbook of collected postage stamps of Gandhi, 1869-1948, Indian statesman.
Keywords: Gandhi -- Mahatma -- 1869-1948 -- On postage stamps